Comparative pharmacokinetics and dosage regimen of enrofloxacin in febrile and afebrile goats - KUMAR, UDAY; SINHA, S P; JAYACHANDRAN, C (The Indian Journal of Animal Sciences, 2014)
Pharmacokinetics of enrofloxacin was studied in afebrile and febrile goats after a single intravenous injection of enrofloxacin (5mg.kg-1). Fever was induced by intravenous injection of E. coli endotoxin (1µg.kg-1). The kinetic profile was described by a 2-compartment open model. The distribution halflife (t½ac) of the drug was 0.42± 0.05 hr in afebrile and 0.51±0.04 hr in febrile goats. The elimination halflife (t½β) of enrofloxacin was 2.90±0.22 hr in afebrile and 2.74±0.16 hr in febrile goats. Vd of 2.43 ±0.32 and 2.42±0.31 L.kg-1 were obtained for enrofloxacin in afebrile and febrile goats, respectively. Almost all kinetic parameters differed nonsignificantly between healthy and febrile goats. This led to nonsignificant change in the dosage regimen of enrofloxacin between afebrile and febrile goats. For maintaining minimum therapeutic concentration (Cpoo min) of 0.12 µg.ml-1, the calculated loading doses (D*) were 5.58±0.75 and 6.39±0.73 mg.kg-1 while maintenance doses (Do) were 5.29±0.77 and 6.10±0.74 mg.kg-1 at the dosage interval(γ)of 12 hr in afebrile and febrile goats respectively.